Plutarch in the religious and philosophical discourse of late antiquity - Roig Lanzillotta, Lautaro.; Munoz Gallarte, Israel. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2012)
The works of Plutarch, notably his Moralia , provide us with exceptional evidence to reconstruct the spiritual and intellectual atmosphere of the first centuries CE. As a priest of Apollo at Delphi, Plutarch was a first range witness of ancient religious experience; as a Middle Platonist, he was also actively involved in the developments of the philosophical school. Besides, he also provided a more detached point of view both regarding numerous religious practices and currents that were permeating the building of ancient pagan religion and the philosophical views of other schools. His combining the insider and the sensitive observer's perspectives make Plutarch a crucial starting point for the understanding of the religious and philosophical discourse of Late Antiquity.